Implementasi Rencana Kerja Tahunan Sekolah Dasar di Era New Normal - Achmad Qhuzairy Qarasyi; Sitti Habibah; Sumarlin Mus (Universitas Kristen Satya Wacana, 2021)
The purpose of this research is to find out the lecturers' strategies in e-learning management to improve learning outcomes in college. The lecturer strategy in managing e-learning includes how to plan, implement, supervise and evaluate online learning (e-learning). This research used a qualitative approach with descriptive methods. The subjects of the study were lecturers who did online learning and were able to improve the results of learning through e-learning. The research instrument used interview guidelines and documentation. Interview, survey, and observation were done to collect the data. Data analysis done by using triangulation techniques. The results of this study shows that the lecturer's strategy in managing e-learning, including 1) Planning, namely drawing up a learning plan on the e-learning website, with a sub-view of RPS (lesson plan), learning achievements, diagnostic tests (pre-test), module materials, learning videos, journal links related to materials, discussion forums, tasks, and absorption tests (posttest).2) Execution, focus on how to solve material problem (reward and punishment) by understanding modules and videos. 3) Supervision is by utilizing the agreed e-learning time, monitoring process through zoom media, video conference and whatsapp group to know the students’ participation in e-learning. 4) Evaluation, with diagnostic tests and absorption tests as an indicator of student atteanity in receiving e-learning materials and independent tasks to improve HOTS (higher order of thinking skills) students. Evaluation in maximizing e-learning content in the website is done with CIPP (context, input, process, and output) so that innovation from lecturers is always increasing.